A Masterclass on developing clinical tools in sport and exercise medicine using principles of clinimetrics. (May 2022) - Buchholtz, Kim; Lambert, Mike; Burgess, Theresa L
Abstract: Musculoskeletal assessment and skill screening tests are regularly used in sports and exercise science to determine performance levels or injury risk in athletes. Many of these tests are used without having undergone clinimetric evaluation. The steps to develop these screening tests and assessment tools should include a structured process according to the clinimetric principles (conceptual and measurement model, reliability, validity, responsiveness, interpretability, burden, alternative forms, and cultural and language adaptation). This systematic process ensures the test measures what it intends to measure and also quantifies the error around the measurement. In this Masterclass we discuss the systematic development and clinimetric evaluation of clinical and performance tests used in sports and exercise science. We use the sport of mountain biking to provide a contextual example of how these principles may be practically applied.